Financial Literacy Among High School Students: An Empirical Baseline for the Türkiye Century Education Model - GOK, Ibrahim Yasar; OZKALE, Abdullah (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study examines the level of financial literacy among high school students in Türkiye and investigates how these levels differ across school types, grade levels, and selected socioeconomic characteristics. The study was conducted in the province of Isparta and employed a structured survey that was conducted to 608 students attending six different types of public high schools. The findings indicate that students’ financial literacy levels are generally low, with comparatively higher scores observed in academically selective schools. Financial literacy is positively associated with parental education level and household income, while no statistically significant differences are found with respect to gender. Twelfth-grade students tend to outperform ninth-grade students; however, the magnitude of improvement across grade levels remains modest. In addition, a notable mismatch emerges between students’ self-assessments of their financial literacy and their objectively measured knowledge, pointing to limited awareness of their own financial competencies. Situated within the framework of the Türkiye Century Education Model, which defines financial literacy as a cross-disciplinary competency, these findings provide an empirical reference point for understanding existing student competencies and for informing the design and interpretation of financial literacy integration within secondary education.